If the sum of first $p$ terms of an $A.P.$ is equal to the sum of the first $q$ terms, then find the sum of the first $(p+q)$ terms.
Let $a$ and $d$ be the first term and the common difference of the $A.P.$ respectively.
Here,
$S_{P}=\frac{p}{2}[2 a+(p-1) d]$
$S_{q}=\frac{p}{2}[2 a+(q-1) d]$
According to the given condition, $\frac{p}{2}[2 a+(p-1) d]=\frac{q}{2}[2 a+(q-1) d]$
$\Rightarrow p[2 a+(p-1) d]=q[2 a+(q-1) d]$
$\Rightarrow 2 a p+p d(p-1)=2 a q+q d(q-1)$
$\Rightarrow 2 a(p-q)+d[p(p-1)-q(q-1)]=0$
$\Rightarrow 2 a(p-q)+d\left[p^{2}-p-q^{2}+q\right]=0$
$\Rightarrow 2 a(p-q)+d[(p-q)(p+q)-(p-q)]=0$
$\Rightarrow 2 a(p-q)+d[(p-q)(p+q-1)]=0$
$\Rightarrow 2 a+d(p+q-1)=0$
$\Rightarrow d=\frac{-2 a}{p+q-1}$ .........$(1)$
$\therefore S_{p+q}=\frac{p+q}{2}[2 a+(p+q-1) \cdot d]$
$\Rightarrow S_{p+q}=\frac{p+q}{2}\left[2 a+(p+q-1)\left(\frac{-2 a}{p+q-1}\right)\right]$ [ From $(1)$ ]
$=\frac{p+q}{2}[2 a-2 a]$
$=0$
Thus, the sum of the first $(p+q)$ terms of the $A.P.$ is $0$
Let $\mathrm{a}_{1}, \mathrm{a}_{2}, \mathrm{a}_{3}, \ldots$ be an $A.P.$ If $\frac{a_{1}+a_{2}+\ldots+a_{10}}{a_{1}+a_{2}+\ldots+a_{p}}=\frac{100}{p^{2}}, p \neq 10$, then $\frac{a_{11}}{a_{10}}$ is equal to :
A number is the reciprocal of the other. If the arithmetic mean of the two numbers be $\frac{{13}}{{12}}$, then the numbers are
If the first term of an $A.P.$ is $3$ and the sum of its first $25$ terms is equal to the sum of its next $15$ terms, then the common difference of this $A.P.$ is :
If the numbers $a,\;b,\;c,\;d,\;e$ form an $A.P.$, then the value of $a - 4b + 6c - 4d + e$ is
If $\log _e \mathrm{a}, \log _e \mathrm{~b}, \log _e \mathrm{c}$ are in an $A.P.$ and $\log _e \mathrm{a}-$ $\log _e 2 b, \log _e 2 b-\log _e 3 c, \log _e 3 c-\log _e a$ are also in an $A.P,$ then $a: b: c$ is equal to